THE GIANT'S TRAIL: MOBILITY AND EXCHANGE OF WHALES AND THEIR BY-PRODUCTS IN ANTIQUITY (1ST CENTURY BC-5TH CENTURY AD) - Antonio Ruiz SÁNCHEZ; Sebastián Uribe RODRÍGUEZ (Journal of Ancient History and Archaeology, 2024)
This research analyzes the role of whales and their by-products as the epicenter of Eurasian exchange networks during Antiquity. To this end, we examine the available knowledge on the biology and behavior of these cetaceans. Two paradigms of transcontinental connections are presented: one through the consumption of whale meat and the other through the circulation of luminescent pearls. Based on this premise, we identify three key points where these animals concentrated their activity: the European Atlantic façade, the Mediterranean coast, and the Indian subcontinent. Regarding the nature of these connective dynamics, there was a conscious exchange of whale-related products. However, its scope was variable. Thus, we propose the coexistence of regional spaces where small-scale whaling was conducted to meet local needs, alongside large Eurasian exchange networks, which are more difficult to trace.